KONSEP TEORI BELAJAR HUMANISTIK DALAM IMPLEMENTASI NILAI-NILAI PENDIDIKAN AGAMA ISLAM - Alfita Choirun Amalia; Munawir Munawir (Aulada : Jurnal Pendidikan dan Perkembangan Anak, 2021)
Abraham Maslow and Carl Ransom Rogers argue that basically humans are special creatures, have the potential and motivation, in the concept of humanistic learning theory is a learning process aimed at humanizing humans, learning success is marked when students recognize themselves and their environment well. Students are faced with targets to achieve the maximum possible level of self-actualization. The principle of humanistic learning rests on the principle of freedom and individual differences. In Islam, the principle of humanizing humans is very much in line with the task of being the vicegerent of Allah on earth. The concept of humanistic learning is in line with the values ​​of Islamic education including: the value of monotheism (integrity), equality and liberation, which upholds respect for humanity, mutuality, and good relations with humans, as well as the value of benefit. With a good teaching and learning climate, it will foster a wider benefit. This research is a type of qualitative research that is included in library research, which is research that collects data from various literatures under study, not limited to books, but also documentation material. things or variables in the form of notes, transcripts, books, newspapers, magazines, and so on. While the analysis uses content analysis, which describes and provides an understanding of the text that has been described, while the technical analysis of the data uses content analysis.